Mixed Methods Approach in Researching EFL Learners’ Motivation - Adara, Reza Anggriyashati; Ahmad, Ismail Sheikh; Victorynie, Irnie (JEES (Journal of English Educators Society), 2024)
As mixed-method approach has gained renewed interests of researchers, a review toward the use of mixed-method to investigate EFL learners’ motivation will contribute as a help for future researchers. The present paper attempts to provide a systematic review by synthesizing research articles related to EFL learners’ motivation which used mixed-methods as their research approach. After screening 3,092 research articles on the aforementioned topic, 16 research articles were included into a final systematic map for analysis. An in-depth review shows that questionnaires and sequential explanatory approach are mostly used by the researchers to investigate EFL learners’ motivation. Although selected studies were performed in different countries with diverse theoretical backgrounds, the majority of studies were directed toward university students, resulting in lack of studies on younger EFL learners. The implications for future studies are also discussed for the consideration of researchers in the near future.